Akira Kurosawa Sinemasında Gücün Gölgesinde İktidar, Kimlik ve Yozlaşma: "Kagemusha" ve "Ran" Filmlerinin Karşılaştırılması. - Öztürk, Ali (Electronic Turkish Studies)
Akira Kurosawa's films Kagemusha (1980) and Ran (1985) center on the themes of power, identity, and corruption, examining the effects of the concept of power on individuals and society on a cinematographic and narrative level. In this study, the two films in question are examined in the context of Michel Foucault's theory of power, Sigmund Freud's psychoanalytic concepts, and Carl Gustav Jung's shadow archetype. While Kagemusha discusses the representative nature of power through the replacement of a real ruler by a shadow warrior (double), Ran depicts the process of the collapse of power through power struggles within a dynasty. In line with Foucault's disciplinary understanding of power, in Kagemusha, power is seen to have become a structure independent of the individual, while in Ran, the chaotic order that emerges with the disintegration of centralized authority is examined. Within the framework of Freud's concepts of ego, id and superego, the identity crisis of the main character in Kagemusha and the transformation he experiences under the pressure of the superego are analyzed, while in Ran, Lord Hidetora's turning to the id as he loses his authority and losing his sanity are analyzed. In the context of Jung's shadow archetype, the characters' reckoning with themselves and their pasts in both films are examined, and the connections between identity construction and personal collapse processes are discussed. In addition, how Kurosawa deepens these themes through cinematographic narration is also examined. The use of color, light-shadow compositions, camera movements and spatial design reinforce the psychological states of the characters and the nature of power on a visual level.